Mycenolide A, new butenolide from a marine sediment-derived bacterium Streptomyces sp. 4054. Issue 20 (17th October 2020) - de Oliveira, Josiane A. Monteiro; Williams, David E.; Andersen, Raymond J.; Sarragiotto, Maria H.; Baldoqui, Debora C.
Abstract: Streptomyces sp. 4054, isolated from marine sediments, produced a new butenolide, mycenolide A (1 ), along with five known butenolide derivatives (2 –6 ). The structures of the compounds were established based on 1D- and 2D-NMR spectroscopic analysis, circular dichroism, and mass spectrometry data. The antimicrobial activity of the crude extract of the marine bacteria Streptomyces sp. 4054 was evaluated, showing good results against Bacillus subtilis and MRSA. Abstract :